Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.foodhyd.2020.105937
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of citrus pectin in low-moisture environment – Investigation of backbone depolymerisation

Abstract: Thermal degradation of modified pectin samples with varying molecular structure during storage was recently studied at 60 °C and 80% relative humidity (rh) for 28 days. Demethoxylation and depolymerisation were identified as main degradation reactions. The present paper aims on improving the understanding of the different depolymerisation reactions and their interplay with demethoxylation during storage. Therefore, thermal degradaton of acidic and alkaline demethoxylated pectins was studied at a further reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 46 publications
8
25
0
Order By: Relevance
“…Comparable values for this signal are described also by other references (Chylinska, Szymanska-Chargot, & Zdunek, 2016, Coimbra et al, 1999, the signal maximum may partly depend on residual water in the sample. Similar differences with respect to the carboxylate signal were also found in a corresponding paper (Einhorn-Stoll et al, 2020), comparing acidic and alkaline demethoxylated pectin (alkaline demethoxylation was performed using 0.5 M NaOH). The signal at 1730 cm -1 was nearly unchanged after sodium ion loading, probably due to the overlay of the carboxyl groups and the methoxyl group signals and the nearly constant DM (LMP+Na: 41.4 ± 0.8% and LMP: 42.8 ± 0.1%).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Comparable values for this signal are described also by other references (Chylinska, Szymanska-Chargot, & Zdunek, 2016, Coimbra et al, 1999, the signal maximum may partly depend on residual water in the sample. Similar differences with respect to the carboxylate signal were also found in a corresponding paper (Einhorn-Stoll et al, 2020), comparing acidic and alkaline demethoxylated pectin (alkaline demethoxylation was performed using 0.5 M NaOH). The signal at 1730 cm -1 was nearly unchanged after sodium ion loading, probably due to the overlay of the carboxyl groups and the methoxyl group signals and the nearly constant DM (LMP+Na: 41.4 ± 0.8% and LMP: 42.8 ± 0.1%).…”
Section: Resultssupporting
confidence: 82%
“…Major alterations in the ATR-FTIR signals (Fig. 2b, c) due to depolymerisation of the pectin samples were similar to those discussed more detailed in a corresponding paper (Einhorn-Stoll et al, 2020).…”
Section: Impact Of the Addition Of Sodium Ions On Thermal Degradation During Storagesupporting
confidence: 82%
“…With this value, and the constants for Mango pectin used (K = 1.40x10 -6 dL g -1 ;  = 1.34) [34] was calculated the MWmean = 55909.76 g mol -1 or 55.91 kDa. The molecular weight obtained was within the previously reported average range for pectin , closer to the lower end of the range [10] which could be an indication of the degradation suffered by pectin during its extraction due to temperature and its de-polymerization to monosaccharides or oligosaccharides [43,44]. The molecular weight is usually directly associated to the strength of the gel formed by the pectin, due to the number of junction zones that can be formed per molecule affects the extent of cross-linking, however, low molecular weights do not affect pectin emulsifying properties or its ability to form hydrogels [15].…”
Section: Intrinsic Viscosity and Viscometric Molecular Weightsupporting
confidence: 82%
“…According to Table 1, it was observed that yield increased with respect to extraction time and temperature, nevertheless, statistical analysis showed that temperature is the main factor who affected the pectin yield extraction (Online Resource 1) since no significant differences between time and temperature vs time interaction were detected. This behavior may be explained by the fact that thermal degradation of pectin occurred, as a consequence of a prolonged time of exposure to high temperatures causing a de-polymerization to monosaccharides or oligosaccharides that could be reflected in low molecular weights [43,44]. It is also interesting to note that the yield increased as the temperature increased, possibly due to an increment in the solubility of the pectin before of being degraded [24].…”
Section: Time and Temperature Effect On Extraction Yieldmentioning
confidence: 99%
See 1 more Smart Citation